Association between abnormal arterial stiffness and cardiovascular risk factors in people with chronic spinal cord injury. (March 2017) - Miyatani, Masae; Alavinia, S Mohammad; Szeto, Maggie; Moore, Cameron; Craven, B Catharine
Aims: To describe the association between cardiovascular risk factors and abnormal arterial stiffness, defined by a carotid-femoral pulse wave velocity ≥ 10 m/s, in patients with chronic spinal cord injury (SCI). Methods: Ninety consenting adults with chronic SCI (C1–T10 ASIA Impairment Scale A–D) participated in this cross-sectional study. The cardiovascular risk factors considered included age, sex, duration of injury, neurological level of injury (C1–T1, tetraplegia; T2–T12, paraplegia), age at injury, impairment scale category, supine resting systolic blood pressure, diastolic blood pressure, mean arterial pressure, heart rate, leisure time physical activity, treated hypertension, treated hyperlipidemia, diabetes, lipid profiles, fasting blood glucose, glycated hemoglobin, and C reactive protein. Logistic regression analysis was used to determine the association between abnormal arterial stiffness and dichotomized cardiovascular risk factors. Results: Dichotomized variables significantly associated with increased arterial stiffness were: age ≥ 52 years (OR 22.1, CI 4.28–113.99); systolic blood pressure ≥ 130 mmHg (OR 11.76, CI 2.89–47.88); heart rate ≥ 62 bpm (OR 6.62, CI 1.33–33.03); and paraplegia (OR 4.26, CI 1.00–18.33). The area under the receiver operating characteristic curve for probability of arterial stiffness was 0.920 (95% CI 0.861–0.978, p < 0.001). Conclusions: Age, resting systolic blood pressure, resting heart rate, and neurological level of injury can identify patients at high risk of elevated arterial stiffness in the population with chronic SCI.